O Direito fundamental da proteção à saúde e segurança do consumidor: recall de medicamentos no Brasil no contexto da segurança humana - Brasileiro, Juliana Barbalho (2018)
The main challenge of this work is to unveil and understand the Brazilian drug recall procedure, as well as to investigate whether it respects the consumer's fundamental rights to information, health and safety and, consequently, dignity. In addition, considering the globalized contemporary society's complexity and risks, we seek to analyze this process by taking into regard the concept of human security, since it presents greater coherence in facing today's risks and dangers. Firstly, a study was carried out in order to understand the full extent of the right to health in the Brazilian legal system, as well as the eminently protective perspective of this fundamental right in the Consumer Defense Code. Secondly, through the perception of the need for a holistic, transdisciplinary and integrated vision for development promotion, society was investigated through sociology, the concepts of society of risk and consumer society, and the concept of human security, a macroconcept spread by UN as a more adequate perspective to contain the multiplicity of risks of the present time. In that regard, emphasis was placed on the instrumentality of consumer law in the promotion of human security by guaranteeing the offer of better quality medicines to consumers and in consumer empowerment, through the provision of information by suppliers and by the State. Third, we examined the Brazilian recall procedure through the legal-normative dimension, observing the Consumer Code, the Ministry of Justice Order No. 487 and Anvisa Resolution No. 55/2012; and the empirical dimension, through the analysis of open recall data extracted from Anvisa and Senacon, as well as from procedures instituted in the 1st Consumer Prosecutor's Office of João Pessoa. At the end of this research, it was concluded that the drug recall procedure is ancillary to Anvisa and to the pharmaceutical laboratories, frontally injuring the basic consumer rights to information, health and safety, and, therefore, alienating the population regarding deviations from drug quality, hurting the fundamental right to consumer protection, leading to risks both in the public and individual health spheres, and colliding against the human security perspective.